Intraspecific variation and population ecology of Sinanodonta woodiana (Bivalvia, Unionidae) in connection with the introduction of this species in Ukraine - PavluchenkoО.; Yermoshyna, T. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
The bivalve mollusc Sinanodonta woodiana Lea, 1834, Chinese pond mussel is a species that quickly colonizes new territories. The article presents the results of research of the morphology and ecology of the Chinese pond mussel from a Repida River (Matroska Village, Odessa Oblast) and a pond in the Hnylop’yat River basin (Romanivka Village, Zhytomir Oblast). The biomass, density, age and sex structure of the populations of these animals were analyzed. The biomass of molluscs is 227.1 and 133.5 g/m2 from the Repida River and a pond in the Romanivka Village, respectively, the density is 1.8 and 0.5 ind./m2. The age structure of the population of S. woodiana is formed by juveniles (the number of 2–3 year old molluscs is 39.5 and 57.1% of two biotopes, respectively), individuals of middle age (4–6 years old – 51.2 and 38.1%) and individuals of the senior group (9.3 and 4.8%). The ratio of age groups in the age structure is 0.8 : 1 : 0.2 for molluscs from the River Repida and 1.5 : 1 : 0.1 for a S. woodiana from the pond. In the sex structure of the molluscs from Repida River males dominated (female: male ratio is 0.7 : 1), but in the sex structure of the investigated group from a pond females were quantitatively superior to males (1.3 : 1). The presence of a significant proportion of young individuals indicate an active reproduction of the local populations. We found glochidia in the gills of females of S. woodiana with a shell length of 9.3–17.5 cm. That is, even with slow growth rates of molluscs in a reservoir with a natural temperature condition of northern Ukraine, they are capable of reproduction at 2 years of age. The data on morphometry of the shells of Chinese pond mussels and biotopical preferences of investigated population of these mollusсs are given. The high level of morphological variability of the shells of S. woodiana, in particular their shape and color, is presented. In the river near the Matroska Village, the average length of a shell is 106±9.7 mm. Molluscs from the pond in the Romanivka Village have larger sizes (132.4±6.9 mm). S. woodiana have a relatively high, short (H/L index value is 0.68 and 0.61 in molluscs from the Repida River and a pond in the Romanivka Village, respectively) and rather convex shell (W/L index is 0.37 and 0.39). After acclimatization under the new conditions, a change in the morphometric indices of the shell in mollusсs from the pond in the Romanivka Village is noticeable. Thus, a statistically significant decrease in the H/L index and an increase in the W/H index in mollusсs from the pond were noted. There were no statistically significant differences in the W/L index. Consequently, mollusсs, introduced into the pond, had an absolute increase in the size of the shell and a relative decrease in its height. The low water temperature does not limit the spread of S. woodiana.